Cardiovascular Manifestations of Hepatorenal Syndrome - da Silva, Marielly; Thaís Augusta Quirino Esteves; Thiago Mendonça Estrela Nascente; Luis Felipe Brito Beffart; Izabella Trevisan Alves; Vinicius Trevisan Alves; Rejayne Carvalho branquinho; Lívia de Oliveira Cardoso; Isabela Machado de Souza; Danillo Gondim da Silva Filho (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Hepatorenal syndrome (HRS) is a severe complication of liver cirrhosis and other advanced liver diseases, characterized by a rapid deterioration of renal function in patients with liver failure. This syndrome results from a complex alteration in renal hemodynamics, leading to significant cardiovascular manifestations. HRS is manifested through abnormalities in renal perfusion, which are often associated with reduced blood pressure, increased peripheral vascular resistance, and decreased cardiac output. Objective: To analyze the cardiovascular manifestations associated with hepatorenal syndrome, focusing on understanding the pathophysiological mechanisms, the effects on the cardiovascular system, and the available management strategies. Methodology: The methodology was based on the PRISMA checklist guidelines to ensure transparency and rigor in the review. Searches were conducted in the PubMed, Scielo, and Web of Science databases using descriptors such as "hepatorenal syndrome," "cardiovascular complications," "hypotension," "vascular dilation," and "acute renal failure." The selected articles were those published in the last 10 years. Inclusion criteria included: studies discussing cardiovascular manifestations of HRS, clinical studies with relevant hemodynamic data, and articles providing a detailed analysis of cardiovascular pathophysiology in HRS. Exclusion criteria included: studies outside the defined time scope, articles not directly addressing cardiovascular aspects of HRS, and publications lacking substantial empirical data. Results: The main topics identified included significant changes in cardiovascular function, such as arterial hypotension and increased systemic vascular resistance. The review revealed that HRS is frequently accompanied by reduced cardiac output and changes in circulatory system dynamics, which can exacerbate liver failure. It was also observed that treating HRS often requires specific strategies to manage cardiovascular effects, such as the use of vasoconstrictors and diuretics. Conclusion: Hepatorenal syndrome is a complex condition with significant impacts on the cardiovascular system. Cardiovascular manifestations of HRS include hemodynamic changes that exacerbate liver failure and present considerable therapeutic challenges. Understanding these aspects is crucial for developing effective treatment strategies and improving the prognosis for patients with HRS.